2013
DOI: 10.1086/673155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antibiotic Use during Hospitalization on the Development of Gastrointestinal Colonization with Escherichia coli with Reduced Fluoroquinolone Susceptibility

Abstract: OBJECTIVE Infections due to fluoroquinolone-resistant Escherichia coli (FQREC) are associated with significant morbidity and mortality. Fluoroquinolone resistance likely arises at the level of gastrointestinal colonization. The objective of this study was to identify risk factors for the development of FQREC gastrointestinal tract colonization in hospitalized patients, including the impact of antibiotics prescribed during hospitalization. DESIGN A prospective cohort study was conducted from 2002 to 2004 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Unfettered antibiotic use has been implicated as one of the key factors driving global increasing antimicrobial resistance [ 1 ]. Studies in other settings have demonstrated that antibiotic administration and ICU admission are associated with development of antibiotic-resistant bacterial stool colonization during the course of a hospitalization, but used longer intervals between enrollment and follow-up [ 28 , 36 ]. The finding that initial empiric antibiotic choice can also significantly impact this process is concerning, especially given how commonly third generation cephalosporins are used in India and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Unfettered antibiotic use has been implicated as one of the key factors driving global increasing antimicrobial resistance [ 1 ]. Studies in other settings have demonstrated that antibiotic administration and ICU admission are associated with development of antibiotic-resistant bacterial stool colonization during the course of a hospitalization, but used longer intervals between enrollment and follow-up [ 28 , 36 ]. The finding that initial empiric antibiotic choice can also significantly impact this process is concerning, especially given how commonly third generation cephalosporins are used in India and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The potentially adverse consequences of increased prescriptions of cephalosporins rather than oral penicillin and amoxicillin are sufficiently demonstrated for the outpatient sector in our view, especially with regard to antibiotic-associated Clostridium difficile infections (24)(25)(26)(27). Data for selection of gram-negative bacteria that are extended-spectrum beta-lactamase (ESBL)-positive or otherwise resistent to cephalosporins are less certain but still plausible (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies did change the pooled results. Specifically, when we removed the studies of Han et al, [34] the heterogeneities for cancer and cardiovascular disease were distinctly reduced evidently by I 2 decreased from 75 to 40% and from 69 to 46%, respectively. After using a fixed-effects model, the ORs and the corresponding 95% CIs for cancer changed from 1.66 (0.96, 2.85) to 2.07 (1.57, 2.75) and from 1.76 (1.02, 3.04) to 2.28 (1.66, 3.12).…”
Section: Sensitivity Analysesmentioning
confidence: 95%